Ecological Epistemology In Indonesian Philosophical Thought Tracing The Roots Of The Concept Of Alam (Nature) In Nusantara Philosophy - Judijanto, Loso; Perera, Dilshan; Nowak, Andrzej (Journal of Humanities Research Sustainability, 2025)
Background. The concept of alam (nature) in Indonesian philosophical thought reflects a deep integration of ecological understanding, cultural wisdom, and spiritual values. Rooted in the diverse traditions of the Nusantara archipelago, alam embodies a worldview where the environment is not merely a physical space but a living system interconnected with human existence and morality. Despite its richness, the epistemological foundations of alam have received limited scholarly attention, particularly in relation to ecological philosophy. Purpose. This study aims to trace the roots of ecological epistemology in Indonesian thought by examining the cultural, historical, and philosophical constructions of alam across various local traditions. Method. A qualitative philosophical approach was employed, combining hermeneutic analysis of classical texts, oral traditions, and indigenous proverbs with comparative interpretation against contemporary ecological philosophy. Results. Findings reveal that the Nusantara concept of alam integrates cosmological balance, relational ethics, and community-based environmental stewardship. These elements parallel, and in some cases anticipate, modern sustainability principles while maintaining distinctive cultural expressions. Conclusion. The study concludes that ecological epistemology in Indonesian philosophy offers a valuable framework for rethinking environmental ethics in the global context, providing culturally rooted strategies for ecological resilience and sustainability.